Respuesta :
Answer:
The composition of the two functions are [tex](fog)(x)=f(g(x))=x^2-6x+9[/tex] and [tex](gof)(x)=g(f(x))[/tex]
Step-by-step explanation:
Given two functions are
[tex]f(x)=^2[/tex]
and [tex]g(x)=x-3[/tex]
Now to find the composition of f and composition of g and f
ie, [tex](fog)(x)=f(g(x))[/tex]
and [tex](gof)(x)=g(f(x))[/tex]
[tex](fog)(x)=f(g(x))[/tex]
[tex]=f(x-3)[/tex]
[tex]=(x-3^2)[/tex]
Now to find the composition of f and composition of [tex]=x^2-2x(3)+3^2[/tex]
[tex](fog)(x)=x^2-6x\div 9[/tex]
[tex](gof)(x)=g(f(x))[/tex]
[tex]=g(x^2)[/tex]
[tex](gof)(x)=x^2-3[/tex]
The composition of the two functions are [tex](gof)(x)=g(f(x))=x^2-3[/tex]
Answer:
(gof)(x)=g(f(x))(gof)(x)=g(f(x))
hope it helps
please mark Brainliest